First occurrences of Nerocila bivittata on Dusky Grouper (Ephinephelus marginatus) and Mottled Grouper (Mycteroperca rubra) - ÇELIK, S.Y.; KORUN, J.; GÖKOĞLU, M. (Journal of the Hellenic Veterinary Medical Society, 2020)
The parasitic Isopod Nerocila bivittata was collected from caudal fins and body surface of dusky grouper (Ephinephelus marginatus) and mottled grouper (Mycteroperca rubra) captured by commercial trawl vessels as non-target species from Antalya Bay which is located in the eastern Mediterranean coast of Turkey. The parasites caused typically hemorrhages on caudal fins of both hosts. The parasitic isopod was identified as Nerocila bivittata which has not been reported from groupers in the worldwide. The study represents new hosts and geographical records.